Morocco. - Bainbridge, James, ....- (Footscray : Lonely Planet, 2011)
Morocco exudes Maghrebi mystique, with medina lanes leading to souqs and riads, camels disappearing into the Sahara and Berber villages perched in the High Atlas. Grab a mint tea and enjoy the show.
Keywords: Marokko -- Reisgidsen